Strategic Planning Model to Increase Quality Basic School Education by 2020 - Yapandi Yapandi (Universitas Tanjungpura, 2018)
This paper presents the reality of educational institutions that is, the weakening of the quality and quality of education in general and especially in elementary schools. This is the result of a study involving institutional boards, school committees, school managers (Principals, Vice Deans, Teachers and Program Coordinators) The main issue of this study is